Evaluasi Operasional Depot Air Minum Isi Ulang (DAMIU) di Wilayah Kerja Puskesmas Rambah - Sarah Atyikah; Herniwanti Herniwanti; Novita Rany; Oktavia Dewi; Iswadi Iswadi (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Water a very important basic human need. Currently, water has even become an economic commodity. Based on the results of the annual recapitulation of the RIAU Provincial Report For Rokan Hulu Regency, there are 103 Drinking water Depots and data obtained are 49 Depots Feasible and 59 Depots Unfit for Food Sanitation Hygiene. From the initial data survey, new information was obtained from 7 depots that carried out laboratory examinations from the existing 15 depots. This study aims to evaluate the operations of the Refillable Drinking Water Depot in the Rambah Health Center in 2020. The method used descriptive qualitative research which was conducted in June in the working area of the Rambah Health Center, Rokan Hulu Regency, RIAU Province. With research subjects 5 Refillable Drinking Water Depot, sanitarian officers, Head of Health, Workers and consumers. From the results of interviews and observations, it was found that the knowledge, hygienic sanitation of Refillable Drinking Water Depot owners was inadequate and only some had a Business License the implementation of standard water testing laboratory tests once 6 months is not in accordance with the applicable regulations, namely once 3 months (Permenkes 2002), the source of raw water used 2 Refillable Drinking Water Depot regular wells 3 Refillable Drinking Water Depot wells BOR, Supervision from Sanitarian puskesmas has not been running regularly and optimally due to limited budget and during the Covid pandemic 19.